PENGARUH INTTELLECTUAL CAPITAL TERHADAP PROFITABILITAS PT MAYORA INDAH Tbk - Narsica Ceren; Longginus Gelatan (JURNAL ULET (Utility, Earning and Tax), 2021)
This study aims to determine the condition of the Intellectual Capital at PT Mayora Indah Tbk. In addition, this study examines the effect of intellectual capital on the profitability of PT Mayora Indah Tbk for the period 2005-2018. This research uses descriptive and associative methods. The data analysis process used simple linear regression analysis with SPSS statistics. The data collection technique used documentation. Based on the analysis results obtained a constant value (a) of 1.553 and a linear regression coefficient (b) of 0.016, so that the simple regression equation is formulated to be Y = 1.553 + 0.16X. The results of the study conclude that intellectual capital has no effect on profitability at PT Mayora Indah Tbk